Recent Advances on Drug-Loaded Mesenchymal Stem Cells With Anti-neoplastic Agents for Targeted Treatment of Cancer - Babajani, Amirhesam; Soltani, Pegah; Jamshidi, Elham; Farjoo, Mohammad Hadi; Niknejad, Hassan (Frontiers in Bioengineering and Biotechnology, 2020)
Mesenchymal stem cells (MSCs), as an undifferentiated group of adult multipotent cells, have remarkable anti-tumor features which bring them up as a novel choice to treat cancers. MSCs are capable to alter the behavior of cells in the tumor microenvironment, induce an anti-inflammatory effect in tumor cells, inhibit tumor angiogenesis and prevent metastasis. Besides, MSCs can induce apoptosis and inhibit the proliferation of tumor cells. The ability of MSCs to be loaded with chemotherapeutic drugs and release them in the site of primary and metastatic neoplasms makes them a preferable choice as targeted drug delivery procedure. Targeted drug delivery minimizes unexpected side effects of chemotherapeutic drugs and improves clinical outcomes. This review focuses on recent advances on innate anti-neoplastic features of MSCs and the effect of chemotherapeutic drugs on viability, proliferation, and the regenerative capacity of various kinds of MSCs. It also discusses the efficacy and mechanisms of drug loading and releasing procedures along with in vivo and in vitro preclinical outcomes of anti-neoplastic effects of primed MSCs for clinical prospection.